WUJUD, MAKNA DAN AKUNTABILITAS “AMAL USAHA” SEBAGAI ASET EKONOMI ORGANISASI RELIGIUS FEMINIS - Suryan Widati; Iwan Triyuwono; Eko Ganis Sukoharsono (Jurnal Akuntansi Multiparadigma, 2011)
Abstract: Form, Meaning and Accountability “Amal Usaha” as Economic Asset for Feminist Religius Organization. This research explores the form, meaning and accountability of “amal Usaha” as economic assets in “Persyarikatan Aisyiyah” as religious organization. By using phenomenological approach, the results of the research shows that Aisyiyah as religious organization exerts efforts to gain profit to fulfill the organization need. Further findings show that, first, “amal usaha” as media to do God’s will in the form of “amal (worship)” and second “usaha (effort)” as an economic effort to gain fund. The economic effort needs accounting as accountability tools objective. This asset is expected to be appears in the syari’ah accounting study. Abstrak: Wujud, Makna dan Akuntabilitas “Amal Usaha” Sebagai Aset Ekonomi Organisasi Religius Feminis. Riset ini mengeksplorasi wujud, makna dan akuntabilitas dari “Amal Usaha” sebagai aset ekonomi di “Persyarikatan Aisyiyah” sebagai suatu organisasi religius. Dengan menggunakan pendekatan fenomenelogi, hasil riset ini menunjukkan bahwa Aisyiyah melakukan usaha mendapatkan laba untuk kepentingan organisasi. Temuan lebih lanjut menunjukkan bahwa, pertama, “amal usaha” merupakan media beribadah kepada Tuhan, dan kedua, ia merupakan usaha utuk mendapatkan dana. Usaha ekonomi ini membutuhkan akuntansi sebagai alat akuntabilitas. Aset ini diharapkan dapat muncul di studi akuntansi syariah.